Gene variants within the COL1A1 gene are associated with reduced anterior cruciate ligament injury in professional soccer players - Krzysztof, F.; Cieszczyk, P.; Kaczmarczyk, M.; Maciejewska-Karlowska, A.; Sawczuk, M.; Cholewinski, J.; Leonska-Duniec, A.; Stepien-Slodkowska, M.; Zarebska, A.; Stepto, N. K.; Bishop, D. J.; Eynon, N. (Journal of Science and Medicine in Sport, 2013)
Objectives: To examine the association of the COL1A1 -1997G/T and +1245G/T polymorphisms, individually and as haplotypes, with anterior cruciate ligament ruptures in professional soccer players. Design: Subjects were 91 male professional soccer players with surgically diagnosed primary anterior cruciate ligament ruptures. The control group consisted of 143 apparently healthy male professional soccer players, who were without any self-reported history of ligament or tendon injury. Both subjects and healthy controls are from the same soccer teams, of the same ethnicity (Polish, East-Europeans for ?3 generations), a similar age category, and had a comparable level of exposure to anterior cruciate ligament injury. Methods: Genomic DNA was extracted from the oral epithelial cells using GenElute Mammalian Genomic DNA Miniprep Kit (Sigma, Germany). All samples were genotyped using a Rotor-Gene real-time polymerase chain reaction. Results: Genotype distributions for both polymorphisms met the Hardy-Weinberg expectations in both subjects and controls (p > 0.05). Higher frequency of the COL1A1 G-T (-1997G/T and +1245G/T polymorphisms) haplotype was significantly associated with reduced risk for anterior cruciate ligament rupture (Hap.score -1.98, p = 0.048). The TT genotype was under-represented in the anterior cruciate ligament rupture group. However, this result was not statistically significant (p = 0.084 Fisher's exact test, recessive mode: TT vs GT+GG). Conclusions: Higher frequency of the COL1A1 G-T haplotype is associated with reduced risk of anterior cruciate ligament injury in a group of professional soccer players. Consequently, carrying two copies the COL1A1 G-T haplotype may be protective against anterior cruciate ligament injury.